Clinical and Genetic Characterization of Brazilian Patients with Ataxia and Oculomotor Apraxia. Issue 6 (14th April 2022) - da Costa, Sophia Caldas Gonzaga; de Rezende‐Filho, Flávio c; de Freitas, Júlian Leticia; de Assis Pereira Matos, Paula Camila Alves; Della‐Ripa, Bruno; França, Marcondes Cavalcante; Marques, Wilson; Santos, Mariana; Cronemberger, Igor Vasconcelos Barros; Vale, Thiago Cardoso; Kok, Fernando; Alonso, Isabel; et al.
Abstract: BACKGROUND: Ataxia with oculomotor apraxia (AOA) is characterized by early‐onset cerebellar ataxia associated with oculomotor apraxia. AOA1, AOA2, AOA3, and AOA4 subtypes may present pathogenic variants in APTX, SETX, PIK3R5, and PNKP genes, respectively. Mutations in XRCC1 have been found to cause autosomal recessive spinocerebellar ataxia‐26 (SCAR26) now considered AOA5. OBJECTIVES: To examine a cohort of Brazilians with autosomal recessive cerebellar ataxia plus oculomotor apraxia and determine the frequencies of AOA subtypes through genetic investigation. METHODS: We evaluated clinical, biomarkers, electrophysiological, and radiological findings of 52 patients with AOA phenotype and performed a genetic panel including APTX, SETX, PIK3R5, PNKP, and XRCC1 . RESULTS: We found pathogenic variants in SETX (15 patients), PNKP (12), and APTX (5). No mutations in PIK3R5 or XRCC1 were identified. CONCLUSIONS: AOA2 and AOA4 were the most common forms of AOA in Brazil. Mutations in PIK3R5 and XRCC1 were not part of this genetic spectrum. © 2022 International Parkinson and Movement Disorder Society